2011
DOI: 10.1016/j.pain.2010.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency treatment relieves chronic knee osteoarthritis pain: A double-blind randomized controlled trial

Abstract: Chronic osteoarthritis (OA) pain of the knee is often not effectively managed with current non-pharmacological or pharmacological treatments. Radiofrequency (RF) neurotomy is a therapeutic alternative for chronic pain. We investigated whether RF neurotomy applied to articular nerve branches (genicular nerves) was effective in relieving chronic OA knee joint pain. The study involved 38 elderly patients with (a) severe knee OA pain lasting more than 3 months, (b) positive response to a diagnostic genicular nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
441
3
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(479 citation statements)
references
References 22 publications
17
441
3
18
Order By: Relevance
“…Raadiofrequency neurotomy is used successfully in OA patients [8]: Choi et al [5] investigated the use of RF treatment to alleviate chronic knee osteoarthritis pain. The randomised controlled trial demonstrated greater improvements in pain, function, and satisfaction for patients treated with RF than for controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raadiofrequency neurotomy is used successfully in OA patients [8]: Choi et al [5] investigated the use of RF treatment to alleviate chronic knee osteoarthritis pain. The randomised controlled trial demonstrated greater improvements in pain, function, and satisfaction for patients treated with RF than for controls.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, larger spherical-shaped lesions are produced that accomplish an effective denervation [5]. No one has studied the effect of cooled radiofrequency on genicular nerves: we examined the efficacy of this application to sensory nerves as a novel alternative treatment for refractory knee pain.…”
mentioning
confidence: 99%
“…[10] 2011 yılında yaptıkları randomize kontrollü çalışma ile geniküler sinire RF uygulamasının kronik diz OA ağrısı üzerine etkili olduğunu göstermişlerdir. Aynı yıl yayınlanan Ikeuchi ve ark.nın [20] yaptıkları duyusal sinirlere yönelik RF uygulamasının, ağrı üzerine etkinliğini değerlendirdikleri kontrollü çalışmada, uygulamadan 12 hafta sonra hastaların ağrı şiddeti-nin kontrol grubuna kıyasla azaldığı belirtilmiştir.…”
Section: Discussionunclassified
“…Diz eklemi sinirlerine radyofrekans termokoagülasyon (RFT) yöntemi ile nörotomi yapılması OA ağrı tedavisinde alternatif yöntem olarak ilk kez 2011 yılında Choi ve ark. [10] tarafından tanımlanmıştır. Diz eklemi geniküler sinirler olarak bilinen; femoral, peroneal, safen, tibial ve obturator sinirler tarafından inerve edilmektedir.…”
unclassified
See 1 more Smart Citation